POWER DIFFUSION AS THE THIRD DIMENSION OF COMPLEX INTERDEPENDENCE: CALIFORNIA AND OPENAI AS CASE STUDIES - Todorović, Marina; Šljivančanin, Milica (Srpska politička misao, 2026)
This paper analyzes the diffusion of power as the third dimension of complex interdependence (the first dimension being military and the second economic), a concept developed and later refined by American scholars Robert Keohane and Joseph Nye. By examining diffusion, or the dispersal of power, as one of the phenomena of international relations, the research focuses on subnational and transnational actors. Through two case studies – the U.S. state of California and the organization OpenAI – the paper investigates how economic, technological, and educational resources enable these actors to influence global power flows independently of the nation-state. The example of California demonstrates how a subnational entity can create innovative policies and set global standards in technology, education, and climate change. OpenAI, as a transnational private actor, shows that innovations in artificial intelligence can redefine the distribution of power and impact international relations beyond state structures. The paper illustrates that power diffusion is a dynamic process arising from the interaction of various actors, rather than a static state that can be “possessed”. This process, however, is sometimes conditioned by ethical considerations and almost always by political and commercial constraints. At the same time, the role of subnational and transnational actors, in this interaction, points to a transformation in the nature of influence within the contemporary global order.